Social representations of mask wearing in the general population during the COVID-19 pandemic - Bornand, Elvire; Letourneux, Frédérique; Deschanvres, Colin; Boutoille, David; Lucet, Jean-Christophe; Lepelletier, Didier; Leclere, Brice; Mayol, Séverine; Peiffer-Smadja, Nathan; Birgand, Gabriel (Frontiers in Public Health, 2023)
Introduction Although one of the most prominent interventions against COVID-19, face masks seem poorly adopted by the general population. A growing body of literature has found that using face masks has social meaning. This qualitative study assessed the perceptions, representations and practices of mask wearing in the general population. Methods A qualitative survey by short semi-structured walking interviews was carried out from April to December 2021 in 11 cities in France's Pays de la Loire region. Study locations were selected for their varied geographical, social, and economic characteristics, with urbanized and rural areas. Four domains linked to perceptions of masks and wearing them were explored: (i) evolution in mask wearing, (ii) decision-making methods for wearing and not wearing; (iii) incorporating the mask into way of life; (iv) projecting into the future. Results A total of 116 people were interviewed. Masks marked a shift from the ordinary world to the pandemic. Overall, interviewees considered masks an obstacle to breathing, communication, and social interactions, leading to establishing strategies circumventing the mask mandate. Poor attention was paid to their medical usefulness as an obligatory clothing accessory. Mask-wearing decisions were driven by social relations, common sense, and vulnerability. The greater the feeling of security (i.e., being with close relatives), the less it was worn or worn properly, with decreased attention to others and their health. Most participants did not remember learning to wear a mask. Some were convinced that mask-wearing could not be learned (experiential knowledge). Institutions (school and work) played a central role by facilitating incorporation of masks into daily life. Conclusions This study emphasizes the need to reinforce the individual medical values of face masks to prevent COVID-19. Ambitious education and training programmes should be planned to learn how and when to wear masks. Institutions (work and school) may be critical for this purpose.